Sistem Informasi Manajemen Layanan Jasa Asosiasi Konstruksi - Yanita Wardhani; Ade Eviyanti; Arif Senja Fitrani (Fakultas Teknik Universitas Hamzanwadi, 2023)
The rapid development improvement in Indonesia has had an excessive influential impact in the construction service business sector. Thus, it is necessary to have a construction service management information system. The construction association considers that the management information system needs developing in line with the soaring demand for construction. The aim of this research is to develop a service management information system in construction associations for better performance. The method used in this study is a case or field research, with data collection through observation, interviews, and literature study. The results obtained from the development of a construction service management information system can assist in data processing of Membership Cards (KTA) and Business Entity Certificates (SBU). With this system, it can also help process data more effectively and more efficiently